In silico Approach to Identify Novel Thiazolidin-4-ones Against Staphylococcus aureus - Rajala Srikala, Rajala Srikala (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: The DHFR inhibitors perform a significant role in thymidine synthesis by blocking the DHFR and interference with this pathway inhibits bacterial DNA synthesis. In this article, a molecular docking study followed by in silico pharmacokinetic parameters could be studied as an effective approach to detect newer DHFR inhibitors. Methods: Novel Thiazolidin-4-one derivatives were designed to perform molecular docking studies using Autodock-1.5.6 and identified the hit molecules. The hits were further evaluated for their drug likeliness using the Swiss ADME web server. Results: The binding affinity of the designed ligands towards DHFR was selected based on binding affinities and interaction patterns. Almost all the compounds have good binding affinities in the range of -10.4 to -5.6 and -11.0 to -8.0 compared with that of cognate ligand -7.6 and –7.9 for wild and mutant DHFR, respectively. Conclusion: The results reveal that Thiazolidin-4-ones as DHFR inhibitors and among 56 compounds, except 5 compounds all compounds showing good binding affinities may produce significant anti-staphylococcal activity for further enhancement.